FeS/FeS2 nanoscale structures synthesized in one step from Fe(ll) dithiocarbamate complexes as a single source precursor - Agoro, Mojeed A.; Meyer, Edson L. (Frontiers in Chemistry, 2022)
Nanoscale FeS and FeS2 mixed phases were synthesized by one-pot decomposition of (N-anil-N-piperldtc)Fe1 as FeS#1), (N-piperldtc)Fe2 as FeS#2) and (N-anildtc)Fe3 as FeS#3) complexes as precursors, with the help of tri-n-octylphosphine oxide (TOPO) coordinating solvent. Their morphology, stability, size, optical and structural characteristics were observed using various material characterization instruments. In comparison to the FeS#2 nano-flower shape, FeS#1 and FeS#3 have a uniform nano-rod shape. A one-step decomposition pattern was obtained from the thermal gravimetric analysis (TGA) results with 3% final mass residual. The high-resolution transmission electron microscopy (HRTEM) image reveals an aggregation and size diameter of around 14.47–30.25 nm for the three samples. The optical response between 3.8 and 4.2 eV from the three samples shows that they are inconsiderable materials for solar cells application. The diffraction peaks for the three samples matched well with the FeS/FeS2. These nanoscale materials can be used in a variety of applications, including lithium-ion batteries, biosensors, hydrogen evolution, and multifunctional nanocomposite materials.